"Kids need structure" - Armaline, William T. (2005)
This study illuminates aspects of social life within agencies designed to house homeless adolescents through research conducted at a live-in, emergency youth shelter. The shelter provides physical necessities, safety, life skills, and a "consistent" social environment through its operation as a quasi-total institution. Social life within the shelter is characterized by constant negotiation of the curricular imposition of "structure". External boundaries become more or less permeable as a result of the degrees to which shelter residents and staff challenge or conform to rules meant to define them. Shelter curriculum may be critiqued for treating adolescent homelessness as an individual rather than social proble m, where rules simultaneously emphasize the modification of individual behaviors and serve as social control mechanisms. Shelter residents, whose poverty and homelessness are only marginally connected to personal behaviors or choices, mount (at times) conscious opposition to rules sanctioning their personal freedoms and access to the outside world. - Reproduced.
Keywords: Homeless